BJ-1108, a 6-Amino-2,4,5-Trimethylpyridin-3-ol Analog, Inhibits Serotonin-Induced Angiogenesis and Tumor Growth through PI3K/NOX Pathway. - Suhrid Banskota; Jaya Gautam; Sushil C Regmi; Pallavi Gurung; Myo-Hyeon Park; Seung Joo Kim; Tae-Gyu Nam; Byeong-Seon Jeong; Jung-Ae Kim (PLoS ONE, 2016)
5-Hydroxytryptamine (5-HT) induces proliferation of cancer cells and vascular cells. In addition to 5-HT production by several cancer cells including gastrointestinal and breast cancer, a significant level of 5-HT is released from activated platelets in the thrombotic environment of tumors, suggesting that inhibition of 5-HT signaling may constitute a new target for antiangiogenic anticancer drug discovery. In the current study we clearly demonstrate that 5-HT-induced angiogenesis was mediated through the 5-HT1 receptor-linked Gβγ/Src/PI3K pathway, but not through the MAPK/ERK/p38 pathway. In addition, 5-HT induced production of NADPH oxidase (NOX)-derived reactive oxygen species (ROS). In an effort to develop new molecularly targeted anticancer agents against 5-HT action in tumor growth, we demonstrate that BJ-1108, a derivative of 6-amino-2,4,5-trimethylpyridin-3-ol, significantly inhibited 5-HT-induced angiogenesis. In addition, BJ-1108 induced a significant reduction in the size and weight of excised tumors in breast cancer cell-inoculated CAM assay, showing proportionate suppression of tumor growth along with inhibition of angiogenesis. In human umbilical vein endothelial cells (HUVECs), BJ-1108 significantly suppressed 5-HT-induced ROS generation and phosphorylation of PI3K/Akt but not of Src. Unlike NOX inhibitors, BJ-1108, which showed better antioxidant activity than vitamin C, barely suppressed superoxide anion induced by mevalonate or geranylgeranyl pyrophosphate which directly activates NOX without help from other signaling molecules in HUVECs, implying that the anti-angiogenic action of BJ-1108 was not mediated through direct action on NOX activation, or free radical scavenging activity. In conclusion, BJ-1108 inhibited 5-HT-induced angiogenesis through PI3K/NOX signaling but not through Src, ERK, or p38.